The Role of Financial Knowledge in Enhancing Financial Independence of The Millennial Generation in The Digital Era - Febiastini, Ni Made; Kadang, Juliana; Darman, D.; Risendy, Rian (Golden Ratio of Finance Management, 2025)
This study aims to analyze the influence of financial knowledge on the financial independence of the millennial generation in the digital era. A descriptive quantitative approach was applied, with primary data collected through questionnaires distributed to 50 BPJS Kesehatan KC Palu employees. Using SPSS V.30.0, statistical analysis evaluated the validity, reliability, respondent characteristics, classical assumptions, and variable correlations. The findings show that financial independence is positively and significantly influenced by General Financial Knowledge, Savings and Loans, Insurance, and Investment, both partially and simultaneously. Financial knowledge, including managing finances, understanding risks, and making sensible decisions, is a key foundation for achieving financial independence. This study is limited by the small number of BPJS Kesehatan KC Palu employees as respondents.